Soil areas numerical determination aimed at correction of a building tilt. Issue 1 (June 2021) - Melnikov, R; Pronozin, Y; Stepanova, M; Bartolomey, L
Abstract: The analysis of the soil area in the base of an absolutely stiff building has been proposed in the article. Influencing this area it is possible to correct the tilt. The authors of the paper provide an overview of various methods of the tilt correction. The study of the soil spreading in the basement soil has been carried out; the soil area is less deformed under eccentric loading than under central loading. This area is proposed to be called the area of "deficit" strains. The first series of numerical computations has shown that this area depends only on the tilt of an absolutely stiff building; it is described in accordance with a linear law when using simple geometric shapes: a sector and a segment. The second series of computations has illustrated that when decreasing deformation and strength characteristics of this area, the building tilt is corrected. In here, the entire area of the "deficit" strains is not required to be used, just its basic area incorporating a part of a sector and a segment. These areas are concentrated at the edge of the footing. The optimal range of values for a single coefficient which lowers the basic mechanical characteristics of soil has been established. Conclusions on the computations have been drawn and plan for further research has been proposed.